Relationship between working hours and power of attention, memory, fatigue, depression and self-efficacy one year after diagnosis of clinically isolated syndrome and relapsing remitting multiple sclerosis. - Peter Joseph Jongen; Keith Wesnes; Björn van Geel; Paul Pop; Evert Sanders; Hans Schrijver; Leo H Visser; H Jacobus Gilhuis; Ludovicus G Sinnige; Augustina M Brands; COGNISEC Study Group (PLoS ONE)
The role of cognitive domain dysfunction with respect to vocational changes in persons with Clinically Isolated Syndrome (CIS) and early Relapsing Remitting Multiple Sclerosis (eRRMS) is insufficiently known. We investigated thirty-three patients--14 CIS, 19 eRRMS -, mean (standard deviation [SD]) time since diagnosis 13.5 (4.8) months and mean (SD) Expanded Disability Status Scale (EDSS) score 1.3 (1.1). Patients were assessed on the CDR System, a set of automated tests of cognitive function, which yielded scores for Power of Attention (ms), Continuity of Attention (#), Working Memory (SI), Episodic Memory (#) and Speed of Memory (ms). Work-related items and the confounding variables fatigue, depression, disease impact and self-efficacy, were assessed by self-report questionnaires. Patients had poorer Power of Attention compared to normative data (1187 [161.5] vs. 1070 [98.6]; P<0.0001) and slower Speed of Memory (4043 [830.6]) vs. 2937 [586.1]; P<0.0001). Power of Attention (Pearson r =  -0.42; P<0.04), Working Memory (r = 0.42; P<0.04) and depression r =  -0.41; P<0.05) correlated with number of days worked per week. Fatigue (r =  -0.56; P<0.005), self-efficacy (r = 0.56; P<0.005) and disease impact (r =  -0.46; P<0.05) correlated with number of hours worked per week. Persons who wished to work less had poorer Power of Attention (1247 vs. 1116 ms; P<0.02), those who wished to change job had poorer Episodic Memory (1.35 vs. 1.57; p<0.03). People who reduced working hours within 12 months after diagnosis had higher fatigue and disease impact, and lower self-efficacy. The findings of this pilot study indicate that one year after the diagnosis of CIS and RRMS Power of Attention and Speed of Memory are reduced, that Power of Attention and Memory are associated with a capability of working less hours, and that fatigue, depression and disease impact may negatively, and self-efficacy positively affect working hours.